Transient Receptor Potential Vanilloid 4 Inhibits γ-Aminobutyric Acid-Activated Current in Hippocampal Pyramidal Neurons - Hong, Zhiwen; Tian, Yujing; Qi, Mengwen; Li, Yingchun; Du, Yimei; Chen, Lei; Liu, Wentao; Chen, Ling (Frontiers in Molecular Neuroscience, 2016)
The balance between excitatory and inhibitory neurotransmitter systems is crucial for the modulation of neuronal excitability in the central nervous system. The activation of transient receptor potential vanilloid 4 (TRPV4) is reported to enhance the response of hippocampal glutamate receptors, but whether the inhibitory neurotransmitter system can be regulated by TRPV4 remains unknown. γ-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system. Here, we show that application of transient receptor potential vanilloid 4 (TRPV4) synthetic (GSK1016790A or 4-PDD) or endogenous agonist (5,6-EET) inhibited GABA-activated current (IGABA) in hippocampal CA1 pyramidal neurons, which was blocked by specific antagonists of TRPV4 and of GABAA receptors. GSK1016790A increased the phosphorylated AMP-activated protein kinase (p-AMPK) and decreased the phosphorylated protein kinase B (p-Akt) protein levels, which was attenuated by removing extracellular calcium or by a calcium/calmodulin-dependent protein kinase kinase-β antagonist. GSK1016790A-induced decrease of p-Akt protein level was sensitive to an AMPK antagonist. GSK1016790A-inhibited IGABA was blocked by an AMPK antagonist or a phosphatidyl inositol 3 kinase (PI3K) agonist. GSK1016790A-induced inhibition of IGABA was also significantly attenuated by a protein kinase C (PKC) antagonist but was unaffected by protein kinase A or calcium/calmodulin-dependent protein kinase II antagonist. We conclude that activation of TRPV4 inhibits GABAA receptor, which may be mediated by activation of AMPK and subsequent down-regulation of PI3K/Akt signaling and activation of PKC signaling. Inhibition of GABAA receptors may account for the neuronal hyperexcitability caused by TRPV4 activation.